2015
DOI: 10.1111/juaf.12150
|View full text |Cite
|
Sign up to set email alerts
|

Right-Sizing Cities in the United States: Defining Its Strategies

Abstract: This article explores the right‐sizing paradigm. Currently, in the growing literature on the right‐sizing conception of planning there are not any clearly delineated strategies on what it means to right‐size. Right‐sizing strategies are clearly articulated in this article in an effort to understand this paradigm in a more comprehensive fashion. This is not being done among scholars in this field and is necessary to determine empirically if these strategies improve the quality of life in shrinking cities. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…Disadvantages of urban shrinking can be transformed into advantages when applying appropriate strategies such as smart shrinking [13,65], smart decline [5] and right-sizing. With regard to public spending, an increase of population density can enable reduction of redundant infrastructure, and eventually also the financial burden, as part of a consolidation strategy [66]. The newly cleared-out sites can be used to develop green infrastructure [67,68].…”
Section: Population Density As An Analytical and Normative Indicator mentioning
confidence: 99%
See 1 more Smart Citation
“…Disadvantages of urban shrinking can be transformed into advantages when applying appropriate strategies such as smart shrinking [13,65], smart decline [5] and right-sizing. With regard to public spending, an increase of population density can enable reduction of redundant infrastructure, and eventually also the financial burden, as part of a consolidation strategy [66]. The newly cleared-out sites can be used to develop green infrastructure [67,68].…”
Section: Population Density As An Analytical and Normative Indicator mentioning
confidence: 99%
“…Here, the proverb "prevention is better than cure" proves true (cf. [66]). If we paraphrase Rink et al [11], we can state that Ostrava serves as the "worst practice" city, a city that, despite rising revenues and economy, continues to lose its population, thus creating a problematic future situation.…”
Section: Discusion and Conclusionmentioning
confidence: 99%
“…Hegemonic urban planning practices have relied on an assumption that decline is a sign of a city in poor health, but because urban shrinkage is a structural phenomenon, scholars have argued that the existing growth-oriented paradigm is not a realistic or valid approach for cities dealing with systemic population loss (Bernt, 2009;Martinez-Fernandez et al, 2012;Pallagst et al, 2017;Shetty and Reid, 2013;Weaver and Holtkamp, 2015). Subsequently, the concept of "smart decline" or "right-sizing" has emerged as an alternative strategy (Bontje, 2005;Haase, 2008;Hollander, 2011;Hollander and Németh, 2011;Hummel, 2015;Schilling and Logan, 2008).…”
Section: Background Shrinking Cities and Vacancymentioning
confidence: 99%
“…A more proactive approach to demolition might work in conjunction with the practices of land banking and urban greening. Land banking occurs when a city organization takes ownership of land, either for repurposing it or simply to take it off the market and suppress supply (Hackworth, 2014;Hummel, 2015). Repurposing of land might take the form of urban greening - Haase (2008) and Schilling and Logan (2008) have suggested that right-sizing is an ideal opportunity for implementing green infrastructure programs.…”
Section: Background Shrinking Cities and Vacancymentioning
confidence: 99%
“…Ultimately, smart decline strategies often aim to reduce the city's fiscal burden by reducing and consolidating the amount of urbanized land (Hummel 2014;Rybczynski and Linneman 1999). City officials in cities where the legacy transportation and utility infrastructure systems are much more extensive than currently needed could use eminent domain to achieve "municipal contraction through wholesale decommissioning" to remove the last holdouts from no longer viable neighborhoods (Beckman 2010, p. 394).…”
Section: Planning In Shrinking Citiesmentioning
confidence: 99%